Epigenetic regulation of neural lineage elaboration: Implications for therapeutic reprogramming - Stefan H. Stricker; Magdalena Götz (Neurobiology of Disease, 2021)
The vulnerability of the mammalian brain is mainly due to its limited ability to generate new neurons once fully matured. Direct conversion of non-neuronal cells to neurons opens up a new avenue for therapeutic intervention and has made great strides also for in vivo applications in the injured brain. These great achievements raise the issue of adequate identity and chromatin hallmarks of the induced neurons. This may be particularly important, as aberrant epigenetic settings may reveal their adverse effects only in certain brain activity states. Therefore, we review here the knowledge about epigenetic memory and partially resetting of chromatin hallmarks from other reprogramming fields, before moving to the knowledge in direct neuronal reprogramming, which is still limited. Most importantly, novel tools are available now to manipulate specific epigenetic marks at specific sites of the genome. Applying these will eventually allow erasing aberrant epigenetic memory and paving the way towards new therapeutic approaches for brain repair.